Slow Dieback of Grapevine in South Africa: Stress-Related Predisposition of Young Vines for Infection by Phaeoacremonium chlamydosporum - Ferreira, J.H.S.; van Wyk, P.S.; Calitz, F.J. (South African Journal of Enology and Viticulture, 2017)
Phaeoacremonium chlamydosporum causes slow dieback of nursery vines and young vines in vineyards. In a greenhouse trial it was observed that significantly more inoculated Chenin blanc vines grafted onto rootstock 101-14 Mgt, and subjected to water stress, exhibited dieback symptoms. More plants eventually died compared to inoculated vines not subjected to stress. Inoculation technique (stem inoculation vs soil inoculation) did not significantly affect disease incidence. Extensive plugging of the xylem tissue in inoculated plants was observed, eventually leading to slow dieback of these vines.